A abordagem do tema "origem da vida" em livros didáticos de ciências do Brasil e de Portugal - Souza, Maíra Luana Santos (2017)
Considering the diversity of scientific, philosophical and religious explanations involved in the approach to the theme Origin of Life, a controversial and challenging subject of research and object of teaching, as well as the reduced number of Brazilian academic investigations regarding the approach of this theme in Teaching The aim of the present research was to analyze how the theme Origin of Life is approached in the most adopted collections of Didactic Books of Brazil and Portugal of the curricular component of Sciences for the 6th, 7th, 8th and 9th year of teaching. In this qualitative research, the Content Analysis of Bardin (1977) was used for the systematization, codification and categorization of the data. Also made use of the theoretical contributions of Yves Chevallard's Theory of Transposition Didactics (1989) and the historical, philosophical and theoretical references of specific areas of Science used in the bibliographic survey on the subject. The results show that the approach of the subject is not restricted only to the year of teaching suggested by the official documents of the education of both countries and also does not recommend only the scientific explanations more accepted at the present time by the scientific community. However, the variety and manner in which the explanations are approached in the books of Brazil and Portugal differ, suggesting different relations of the two countries with the scientific reference sources in which the knowledge of the curriculum resides. It was also observed for both countries the decontextualization and reduction of the experiments and hypotheses approached with their production contexts, besides the isolation of the theme with closely related concepts, worrying about their impact in the teaching-learning of the subject, considering that the Science Didactic Books are, besides a source of lesson planning, support for teaching-learning activities and, even, a source of studies for teachers and students. The present research contributed with reflections on the Teaching of Sciences and indicates the need for more investigations on the teaching of the theme Origin of Life.